TaNBP1, a guanine nucleotide-binding subunit gene of wheat, is essential in the regulation of N starvation adaptation via modulating N acquisition and ROS homeostasis - Zhipeng Liu (BMC Plant Biology, 2018)
Abstract Background Nitrate (NO3 −) is the major source of nitrogen (N) for higher plants aside from its function in transducing the N signaling. Improving N use efficiency of crops has been an effective strategy for promotion of the sustainable agriculture worldwide. The regulatory pathways associating with N uptake and the corresponding biochemical processes impact largely on plant N starvation tolerance. Thus, exploration of the molecular mechanism underlying nitrogen use efficiency (NUE) and the gene wealth will pave a way for molecular breeding of N starvation-tolerant crop cultivars. Results In the current study, we characterized the function of TaNBP1, a guanine nucleotide-binding protein subunit beta gene of wheat (T. aestivum), in mediating the plant N starvation response. TaNBP1 protein harbors a conserved W40 domain and the TaNBP1-GFP (green fluorescence protein) signals concentrate at positions of cytoplasm membrane and cytosol. TaNBP1 transcripts are induced in roots and leaves upon N starvation stress and that this upregulated expression is recovered by N recovery treatment. TaNBP1 overexpression confers improved phenotype, enlarged root system architecture (RSA), and increased biomass for plants upon N deprivation relative to the wild type, associating with its role in enhancing N accumulation and improving reactive oxygen species (ROS) homeostasis. Nitrate transporter (NRT) gene NtNRT2.2 and antioxidant enzyme genes NtSOD1, NtSOD2, and NtCAT1 are transcriptionally regulated under TaNBP1 and contribute to the improved N acquisition and the increased AE activities of plants. Conclusions Altogether, TaNBP1 is transcriptional response to N starvation stress. Overexpression of this gene enhances plant N starvation adaptation via improvement of N uptake and cellular ROS homeostasis by modifying transcription of NRT gene NtNRT2.2 and antioxidant enzyme genes NtSOD1, NtSOD2, and NtCAT1, respectively. Our research helps to understand the mechanism underlying plant N starvation response and benefits to genetically engineer crop cultivars with improved NUE under the N-saving cultivation conditions.